2016
DOI: 10.1002/admi.201600036
|View full text |Cite
|
Sign up to set email alerts
|

Directional Water Transport Fabrics with Durable Ultra‐High One‐Way Transport Capacity

Abstract: Fabrics with automatic one‐way water transport ability are highly desirable for applications in daily life, industry, health, and defense. However, most of the studies on one‐way water transport fabrics only report the qualitative water transport results. The lack of quantitative measure makes it hard to assess the directional transport quality. Here, it is proved that a hydrophilic fabric after being electrosprayed with a thin layer of hydrophobic coating on one side shows one‐way water transport ability. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 47 publications
(61 reference statements)
2
96
0
Order By: Relevance
“…In our previous paper [33], we showed that treatment with NaOH gives the polyester fiber a hydrophilic surface because of the hydrolysis of polyester in alkaline conditions. SU-8 treatment allowed the treated fibers to have a hydrophobic feature.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In our previous paper [33], we showed that treatment with NaOH gives the polyester fiber a hydrophilic surface because of the hydrolysis of polyester in alkaline conditions. SU-8 treatment allowed the treated fibers to have a hydrophobic feature.…”
Section: Resultsmentioning
confidence: 97%
“…To prepare the directional water transport fabric, SU-8/acetone solution was deposited on one side of the NaOH pre-treated polyester fabric using our previously developed method [33]. The chemical structure of SU-8 is shown in Figure 1a and the apparatus for one-side electrospraying treatment is schematically illustrated in Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, unexpected high water content on the coated face was measured by the MMT. This is due to the measurement method where the sensor of MMT slightly penetrates into the fabric (depth around 60 µm [27]), therefore, the water content measured actually reflects the water content in the surface layer around 60 µm.…”
Section: Typical Relative Water Content Curves Of the Fabricsmentioning
confidence: 99%
“…For example, Tian et al [26] used a vapor-phase method to deposit a fluoroalkylsilane on one side of cotton fabric to create directional gating of droplets in air-water system. Zeng et al [27] prepared a one-way water transport fabric by electro-spraying a hydrophobic layer on one side of the fabric. However, most of the current studies only focused on the trans-planar water transport of textile materials, and little research is reported on both trans-planar and in-plane water transport properties.…”
Section: Introductionmentioning
confidence: 99%